Penguatan Perilaku “Ngeloni Anak” Oleh Ibu-Ayah sebagai Upaya Menciptakan Keluarga Harmonis-Seimbang Sejak Dini - Azzam Syukur Rahmatullah (Cendekia: Kependidikan dan Kemasyarakatan, 2016)
One of important aspects in educating children to have a harmonious, balanced, and lasting family is to concern on parenting since early times. One of the ways is to hug a child. This paper discusses the importance of child development so they can build a harmonious family. When the parent demonstrates their affections to their children by hugging, the children will get a double touch from their parent (father and mother) and they do not get the touch from one of them. Hugging children has a big role to child development in the future. The more the parent gives a sincere affection, positive situation, friendship, the more children will get strong of personality. A good and health personality will affect self-children positively when they build a family to become a harmony family. On the contrary, the less the parent give a warm hugging likes no affections and sincerity, derision, insult and reproach; the more the children will get a sick personality. Such personality will be a problem for children either in the present times or during the development period from childhood to teenage and adult. أحد الجوانب الهامة المؤدية إلى أن تكون أسرة الولد في المستقبل أسرة سعيدة مستقرّة وفي دوامهما هو نمط الحضانة الصحيحة منذ البداية.  ومن كيفيات الحضانة والتربية هي تحضين الولد ومعانقته. حاولت هذه المقالة نقاش أهمية " معانقة الأبناء"  لنشوئهم وتطوّرهم حتى كوّنوا في المستقبل أسرة سعيدة مستقرّة. بهذه العملية - معانقة الأبناء- سيحصل الأبناء على اللمستين ( المعانقة الحارة من الوالدين) لا من طرف واحد فقط( الأم). ومعانقة الأبناء لها دور كبير في نموّ الأبناء وتطوّرهم في المستقبل. إذا تكرّرت هذه المعانقات – وفيها الرحمة والشفقة والدوافع الإيجابية، والـتأمين والمصاحبة – أعطت للأبناء فرصا ليكونوا أبناءا ذوي شخصيات قوية سليمة.  وهذه الشخصيات القوية السليمة ستؤثّر إيجابيا على نفوس الأبناء حين تزوّجوا وستصبح أسرتهم أسرة سعيدة. والعكس إذا قلّت هذه المعانقات – فبها قلّت الرحمة والشفقة بل صدر من الوالدين العتاب والتحقير وغيرهما – وستؤي إلى أن تكون شخصية الأبناء ضعيفة مريضة. وهذه الشخصية غير السليمة ستصبح مشكلة لهم في صغرهم وحين أصبحوا شبانا ورجالا.